Pelatihan Promosi dan Pemasaran UMKM Melalui Platform E-Commerce di Kelurahan Bugangan, Semarang - Ika Menarianti; Shofif S Akbar; I’tishom Al Khoiry; Ernawati Saptaningrum; Dhea Rizky Amelia (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia still face various challenges, including access to markets and the lack of skills in utilizing digital technology to expand their market and increase income. With the rise of the digital era, the use of digital technology and e-commerce can be a solution for MSMEs to enhance their competitiveness and expand their market. As consumer behavior shifts towards online shopping, technology-based marketing strategies can become a key driver in boosting the sales of MSME products. E-commerce offers opportunities for everyone to introduce products or services with unlimited marketing reach. Therefore, business organizations must be adept at identifying effective marketing opportunities in the digital era that are both cost-efficient and impactful. The main focus of this community service project is to increase the market share and sales turnover of MSME products in Bugangan Village, Semarang City, through appropriate marketing strategies. The stages of this service begin with preparation. In this stage, the community service team conducts site visits and initial field observations to assess the conditions and challenges faced by the partners directly.  Then, the preparation of materials to be delivered follows. The team prepares materials that are tailored to the needs of Bugangan Village. The third stage is socialization and implementation. As a result of the activities, 20 MSMEs in Bugangan Village, Semarang City, gained knowledge about online or digital marketing, product photography, content creation with Canva, Google My Business, and setting up e-commerce accounts.